Impact of problem-based learning on community nurses' critical-thinking skills. - Abdalla, Rahma (British Journal of Community Nursing, 2026)
Background: Problem-based learning is a meaningful teaching strategy that contextualises theoretical components into clinical knowledge, with the potential to encourage nurses to think critically and solve problems through integration of theory and practice. Problem-based learning may support community nurses to use their own initiative to develop skills relevant to managing complex real-world situations when providing care in patients' homes. Aims: This article explores the impact of problem-based learning on the critical thinking skills of community nurses. Methods: This systematic review used an integrative synthesis approach, combining narrative and thematic analysis to interpret findings across heterogeneous quantitative studies examining the impact of problem-based learning on nurses' critical thinking. Key words were established using a Population, Exposure, Outcome framework. Boolean operators, phrase searching, truncations and wildcards were used for the literature search. Three different databases were used on the EBSCOhost platform, including Academic Search Complete, CINAHL Complete and Medline. Thematic analysis was used to establish themes across the studies and to form an overall impression of the results. Results: The review identified key areas of development reported after exposure to problem-based learning, including knowledge, attitude, perception, self-efficacy, problem solving, clinical reasoning, evaluation skills, performance and competency, motivation and self-directed learning. Some studies also suggested potential benefits for safe and effective nursing care. Conclusions: Problem-based learning strategies may have a positive learning effect that supports the development of nurses' critical thinking and clinical decision making. As the included studies were conducted with student nurses in academic settings and findings were mixed, a rigorous review incorporating mixed-method studies in both practice and academic environments, and including qualified community and district nurses, is needed to confirm or refute these findings. Implications for practice: As problem-based learning may have a positive impact on nurses' critical thinking, there is scope to explore its use as an interactive teaching strategy in practice education, with further research needed to determine its impact on safe and effective nursing care.